Gen Z Teachers Candidates: Perspective on Early Childhood Moral Religious Values Development - Jumiatmoko (Jurnal Pendidikan Anak, 2022)
As teachers and pre-service teachers, Generation Z has unique characteristics. The mindset, interests, and priorities related to religious and moral values ​​in early childhood need to be carefully understood. This study explores qualitative data related to topics of religious and moral values ​​that are of most interest and priority. Data were obtained from 58 (fifty eight) respondents of pre-school teacher bachelor candidates. Respondents were given a structured task in the form of an essay on the priority ideas for developing NAM for early childhood. Completion of tasks is given 7 (seven) days to complete the task. The main analysis was carried out by thematic analysis. The results are categorized into 5 (five) themes and 29 (twenty nine) sub themes. The analysis is carried out in 2 (two) stages. Phase 1 is in the form of grouping data according to Basic Competence (KD) in the aspect of NAM for early childhood. Stage 2 is in the form of determining the topic (correspondence with KD and determining the frequency of occurrence). The themes related to the religious and moral values ​​of early childhood are the most interested and prioritized, namely good behaviour and trust in God, while the least is respect for oneself, others, and the environment. Various factors and typical characteristics of Generation Z are discussed to reveal these findings.